THE INTERNALIZATION OF ASMAUL HUSNA VALUES THROUGH THE DEVELOPMENT OF "AUTHENTIC READING MATERIALS" AS AN EFFORT TO BUILD RELIGIOUS CHARACTERS - Niken Kencono Ungu (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
This research is a report of Nation Character Education which has a purpose as an Effort to Build Religious Character. The author will try to overcome the moral degradation that occurs in students such as bullying, free promiscuity, rah-rah, hedonism by internalizing Asmaul Husna's values into reading courses by developing the learning of authentic reading materials. From here, religious character education will begin to be built.The results of the research include several things. The most important result is a product called a reading textbook that has been internalized with Asmaul Husna's values. This book is the development of authentic reading materials adapted to the syllabus in the reading course being taken by students of the English Education program especially the students of third Semester.The research methodology used in this research is Research and Development (R & D) which will be elaborated qualitatively. After conducted this research, it showed that the book product of authentic reading materials which had been internalized with Asmaul Husna was an effective way to build the students’ character as the effort to overcome the students’ moral degradation. 85% showed that students have a significant increase in their reading ability and also students continue to display increasingly improved behaviors after learning the Asmaul Husna values in their reading textbook. Keywords: Internalization of values, Asmaul Husna, Authentic Reading Materials, Building Religious Character.